HIV RNA Suppression during and after Pregnancy among Women in the HIV Outpatient Study, 1996 to 2015. (20th January 2018) - Patel, Monita; Tedaldi, Ellen; Armon, Carl; Nesheim, Steven; Lampe, Margaret; Palella, Frank; Novak, Richard; Sutton, Madeline; Buchacz, Kate
Objective: To examine HIV viral suppression during/after pregnancy. Design: Prospective observational cohort. Methods: We identified pregnancies from 1996 to 2015. We examined HIV RNA viral load (VL), VL suppression (≤500 copies/mL), and antiretroviral therapy (ART) status at pregnancy start, end, and 6 months postpartum. We estimated risk ratios (RRs) and 95% confidence intervals (CIs) for VL nonsuppression. Results: Among 253 pregnancies analyzed, 34.8% of women exhibited VL suppression at pregnancy start, 60.1% at pregnancy end, and 42.7% at 6 months postpartum. Median VL (log10 copies/mL) was 2.80 (interquartile range [IQR]: 1.40-3.85) at pregnancy start, 1.70 (IQR: 1.40-2.82) at pregnancy end, and 2.30 (IQR: 1.40-3.86) at postpartum. Risk of postpartum VL nonsuppression was also lower among women on ART and with VL suppression at pregnancy end (versus those not; adjusted RR = 0.30, 95% CI: 0.17-0.53). Conclusions: Maintaining VL suppression among US women remains a challenge, particularly during postpartum. Achieving VL suppression earlier during pregnancy benefits women subsequently.